Plant growth regulator-free propagation of Hedeoma multiflora Benth: comparison of morphological and volatile metabolomic aspects of in vitro vs in vivo plants - Diaz Gabutti, Maria Soledad (2023)
The aromatic plant Hedeoma multiflora Benth. is endangered by the overexploitation and the advance of agricultural and urban borders. The objective of this work was to establish an in vitro multiplication protocol for the species without using plant growth regulators (PGRs) and to compare both the morphology and the ability to produce volatile metabolites of the in vitro plants toward wild populations. We were successful in establishing two in vitro plant lines, one initiated from seeds and other from binodal segments. Neither the addition of 1-naphthylacetic acid, kinetin or their combinations improved either growth or multiplication rates which reached 26.4 stems per initial explant after 12 weeks. A comparison toward three wild populations, harvested at both early and late summer time, showed that the morpho-anatomical characteristics of the aerial parts were fairly preserved although in vitro plants displayed more abundant but shorter roots. The profiles of volatile compounds from in vivo and in vitro specimens were quite similar, although hydrocarbon monoterpenes’ fraction was more important in the latter. Pulegone was by far the main volatile metabolite in all the assessed populations while its proportion dropped in the in vitro and in the in vivo plants from late summer with respect to in vivo plants from December. The concentration of the biomarkers, menthone, isomenthone, pulegone and isopulegone, was approximately an order of magnitude lower in the in vitro than in the in vivo plants. Overall, the in vitro biomass production in a PGR-free medium is an appropriate technology for reducing the overexploitation of wild endangered populations and avoiding health safety issues related to the edible consumption of the species.